Hydrogen sulfide generation and emission in urban sanitary sewer in China: what factor plays the critical role?. Issue 5 (3rd April 2019) - Zuo, Zhiqiang; Chang, Jian; Lu, Zhengsheng; Wang, Moran; Lin, Yucong; Zheng, Min; Zhu, David Z.; Yu, Tong; Huang, Xia; Liu, Yanchen
Abstract : Identifying hydrogen sulfide (H2 S) hotspots is critical for preventing/controlling odor and corrosion problems in sewer systems. Abstract : Identifying hydrogen sulfide (H2 S) hotspots is critical for preventing/controlling odor and corrosion problems in sewer systems. However, relatively little is known regarding H2 S hotspots and variation characteristics in China's urban sewer networks. A comprehensive field investigation was carried out on the impacts of sewer structures, season, water flow and wastewater quality on H2 S emission. The results indicated that H2 S diurnal variation mainly followed the dry weather flow fluctuation in gravity sewer networks. The manhole downstream of septic tanks was identified as a H2 S emission hotspot due to potential significant sulfide generation in the septic tanks. The effect of temperature on H2 S emission was related to variations in the sulfide production rate and flow turbulence at different locations in the sewer system. Significant reduction in sulfide concentration was observed with rainfall-derived high water flow rate. The local water quality was identified as a key factor for sulfide generation from different sites along the sewer system. These findings are useful in understanding and predicting H2 S emission in China's sewer systems.